Fundamental movement skills and physical fitness in children: mediating roles of play-based activity and nutritional status a systematic literature review - Intan Maharani; Syahrial Bakhtiar; Wilda Welis; Anton Komaini (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
In this systematic literature review (SLR), we have attempted to bring together the existing body of evidence on the interplay between FMS competency, play-based PA participation, nutritional status, and physical fitness outcomes in children aged 3-18 years. Following the PRISMA 2020 guidelines (Page et al., 2021), a thorough search was done on the Scopus database, which brought out 585 preliminary records. After duplicate removal (n = 47), screening titles and abstracts (n = 538), and assessing full-text eligibility (n = 149), 55 papers ended up fitting the criteria and were used for the final synthesis. Methodological quality was appraised using an adapted FICO (Focus, Information, Context, Outcome) framework, and inter-rater agreement during screening and data extraction was high (Cohen's κ = 0.85). Included studies, published between 2018 and 2026, comprised randomized controlled trials, quasi-experimental and cross-sectional designs, and systematic reviews. Major results from this review point to the fact that: (1) FMS proficiency predicts children's habitual PA levels, especially during play-based situations; (2) both structured and outdoor play-based programs have been shown to be effective in the enhancement of locomotor and object control skills; (3) nutritional status, especially being overweight or obese, not only poses a risk for FMS performance but can also affect cardiovascular fitness; and (4) the development of both motor competence and physical fitness in children is dependent on play, dietary habits, and socioeconomic situation. These conclusions have important theoretical meaning for the ecological dynamics model of motor learning as well as practical implications for physical education content, school health policies, and clinical pediatric guidelines. Longitudinal studies should be the focus of future research as they allow investigating the relationships of all four constructs together while targeting populations that are rarely studied, especially in low- and middle-income regions